2016
DOI: 10.1007/s00198-016-3637-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concomitant vitamin D deficiency or insufficiency on lumbar spine volumetric bone mineral density and trabecular bone score in primary hyperparathyroidism

Abstract: Summary Lower vitamin D and higher parathyroid hormone (PTH) levels are associated with higher volumetric BMD and bone strength at the lumbar spine as measured by central quantitative computed tomography in primary hyperparathyroidism (PHPT), but there are no differences in bone microarchitecture as measured by trabecular bone score (TBS). Introduction The purpose of this study was to evaluate the association between 25-hydroxyvitamin D (25OHD) and volumetric bone mineral density (vBMD) and the TBS at the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
5
15
0
Order By: Relevance
“…This could reflect that vitamin D have an effect upon mineralization but not microarchitecture or may be related to the low sensitivity of TBS. These results are consistent with those described in 2 recent studies in PHPT patients [10,22].…”
Section: Discussionsupporting
confidence: 93%
“…This could reflect that vitamin D have an effect upon mineralization but not microarchitecture or may be related to the low sensitivity of TBS. These results are consistent with those described in 2 recent studies in PHPT patients [10,22].…”
Section: Discussionsupporting
confidence: 93%
“…A lack of association between BMD and circulating concentrations of vitamin D as seen in this study is not unique. There are reports of an absence of association between BMD, as determined by DXA scan, and vitamin D levels in children, 14 adults with primary hyperparathyroidism, 15 obese adults, 16 and Middle Eastern adults. 17 The current findings could be due to the small sample size or bias of the sample population.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors focused on the relationship between vitamin D and TBS in PHPT patients. The first study revealed no differences in TBS values between the three following groups: vitamin D level < 20 ng/mL, 20-29 ng/mL, and ≥ 30 ng/mL even after adjusting for age, sex, weight, and GFR [50]. The second study was designed as an investigator-initiated, double-blind, randomised, placebo-controlled, parallel-group trial and comprised a study group of 46 PHPT patients (35 women, 11 men; mean age 58 years).…”
Section: Primary Hyperparathyroidismmentioning
confidence: 93%